An Overview of Biorefinery Waste for Microbial Production of Green Plastic in a Circular Economy§ - Geethika Gudapati; Sridevi Veluru; Tanmayi Bora; M Tukaram Bai; Anupama Kavya Priya Dwarapureddy; Giri Prasad Reddi; Husam Talib Hamzah (Food Technology and Biotechnology, 2025)
An increasing amount of plastics is being used due to the growing population. Plastic waste pollution has become a major problem, especially in the marine environment, due to the increasing global demand for plastic materials. Bioplastics produced from waste in biorefineries offer a sustainable alternative to traditional plastics by recycling materials that are normally thrown away in the food, farming and manufacturing industries. This technology tackles both the plastic waste crisis and the inefficient use of biomass. By recycling biorefinery waste into bioplastics, the impact on the environment can be reduced, waste minimised and less fossil fuel consumed. Improving material qualities, reducing production costs and optimising the efficiency and scalability of these processes are all ongoing challenges. This review focuses on waste biorefineries for bioplastic synthesis as a sustainable approach to the circular bioeconomy. It also provides a better understanding of environmental sustainability, societal well-being and technological advances in the utilisation of various biorefineries as different substrates and methods for bioplastic synthesis.